2019
DOI: 10.1128/aem.00104-19
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorothioated DNA Is Shielded from Oxidative Damage

Abstract: DNA is the carrier of genetic information. DNA modifications play a central role in essential physiological processes. Phosphorothioation (PT) modification involves the replacement of an oxygen atom on the DNA backbone with a sulfur atom. PT modification can cause genomic instability inSalmonella entericaunder hypochlorous acid stress. This modification restores hydrogen peroxide (H2O2) resistance in the catalase-deficientEscherichia coliHpx−strain. Here, we report biochemical characterization results for a pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Recently, we showed that the Fe‐S cluster of DndC is in the [4Fe‐4S] configuration (Pu et al, ). The cluster has a g value peak of 2.005 at 13 K. The cluster can be deprived off by α,α’‐dipyridyl treatment and reconstituted back using cysteine and (NH 4 ) 2 Fe(SO 4 ) 2 with the catalysis of IscS under anoxic conditions (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we showed that the Fe‐S cluster of DndC is in the [4Fe‐4S] configuration (Pu et al, ). The cluster has a g value peak of 2.005 at 13 K. The cluster can be deprived off by α,α’‐dipyridyl treatment and reconstituted back using cysteine and (NH 4 ) 2 Fe(SO 4 ) 2 with the catalysis of IscS under anoxic conditions (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…(b) The involvement of the iron‐sulfur cluster in the PT reaction. The Dnd protein complex used in the reaction was anoxically reconstituted (dark green, resulting in a [4Fe‐4S] cluster; Pu et al, ), oxically purified (brown, [3Fe‐4S]) or treated using 1 mM α,α'‐dipyridyl (gray), which removed the Fe‐S cluster [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations